International endogenous growth, macro anomalies, and asset prices - Patrick Grüning (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2016)
This paper studies a two-country production economy with complete and frictionless financial markets and international trade in which competition in R&D leads to endogenous new firm creation and economic growth. Current monopolists ("incumbents") and potential new firms ("entrants") compete in developing patents domestically. These innovative firms use both consumption goods in their R&D technologies to capture international technological spillovers. In the model specifications with technology spillover one obtains that (i) the cross-country correlation of consumption growth is lower than the one of output growth; (ii) net exports are negatively correlated with output; (iii) the model matches the high co-movement of stock returns across countries. Furthermore, heterogeneity in the R&D technology bundle home bias parameters for incumbents and entrants enables the model to replicate the empirically rather moderate correlation between the R&D innovation probabilities of incumbents and entrants within a country. Moreover, the model produces a positive value premium. Finally, the exchange rate volatility is decreasing in the amount of technology spillovers.
Keywords: E22; F31; G12; O30; O41; 330; Innovation; Technology Spillover; Endogenous Growth; Long-run Risk; International Finance